Toward a Greener Fabric: Innovations in Natural Dyes and Biomordants for Sustainable Textile Applications - Islam, Shahidul; Jalil, Md. Abdul; Motaleb, K.Z.M Abdul; Saeed, Md. Abu; Belowar, Sanjoy; Rahamatolla, Md.; Hossain, Shahin; Mukit, Md. Abdul; Khan, Ayub Nabi (Sustainability & Circularity NOW, 2025)
The textile industry has historically shifted from natural to synthetic dyes and mordants due to factors such as broader color range, improved colorfastness, and large-scale production efficiency. However, synthetic alternatives raise serious environmental and health concerns owing to their toxicity, nonbiodegradability, and resource-intensive manufacturing. With increasing global emphasis on sustainable and eco-conscious practices, there is renewed interest in natural dyes and biomordants. This review critically examines the resurgence of these bio-based colorants, comparing traditional natural dyes and mordants to modern innovations in terms of performance, environmental impact, and feasibility for industrial use. While natural dyes offer biodegradability and reduced toxicity, they face limitations in color consistency, fastness, and scalability. Advances in biotechnology have led to the development of bioengineered dyes from microorganisms, waste-derived pigments, and biomordants such as chitosan, tannins, and enzymes that address some of these challenges. Additionally, hybrid approaches incorporating nanotechnology are enhancing dye uptake and durability. By integrating insights from materials science and green chemistry, this review outlines the current state and future prospects of natural dyes and biomordants in transforming textile manufacturing into a more sustainable industry.
Keywords: Natural dyes; Biomordants; Sustainable textiles; Eco-friendly dyeing; Bioengineered pigments; Nanotechnology in dyeing